(untitled) (Vietnam Journal of Community Medicine, 2024)
While the high rate of unhealthy living habits is recorded in Men, the impacts of these habits on andrologic health have been still studied limitedly. We conducted a cross-sectional descriptive study on 578 men who came for their first examination for reproductive and sexual health at the Andrology Clinic, Hanoi Obstetrics and Gynecology Hospital. The study showed that 59.7% and 48.4% of men used alcoholic beverages and smoked cigarettes. There were 13.3% and 16.6% of men spontaneously using supplements and unknown-origin traditional products (UOTP) to improve reproductive and sexual health. 67,4% men with abnormal semen analysis were found. Concentration of gonadotropin (FSH/LH) was also higher in the abnormal semen tests group than the normal semen tests group (p<0.05). Men that used UOTP had higher FSH/LH concentrations with a significant decrease in sperm density and motility compared to mens that did not use UOPT (p<0.05). There was no difference in terms of the outcome of semen tests and reproductive hormones between groups that used tobacco, alcohol, and supplements and did not use these factors.